Complementarity Effect of Corporate Advertising in a Multimedia World: A Comparison of Online Advertising and Mass Media Advertising - Chieko Fujisawa; Norihiro Kasuga (International Telecommunications Society (ITS), 2023)
This study analyzes the type of advertisements firms pursue when they engage in Cournot competition, especially when goods are complementary in a multimedia environment. Advertisements are classified into search-linked advertisements for online advertisements and TV commercials for mass media advertisements. Which one should the firm choose? This study also analyzes how corporate advertising strategies affect social welfare and provides insight into the role of advertising in multimedia. A firm's advertisement selection depends on the degree of complementarity and differentiation between advertisements. This analysis also focuses on the advertising strategies of duopoly firms in an extended model, such as hardware firms that are complementary to software products. In that case, both choose mass media advertising when the differentiation is moderate, and this choice raises both aggregate surplus and producer surplus. When advertising complementarity is high for both mass media and online advertising, firms choose different types of advertisements, but social welfare is low. This result is one of the considerations of a firm's sales strategy, how on using advertisements to increase demand and maximize profits.
Keywords: 330; Online media advertising; Mass media advertising; Complementary relationship; Advertising Strategy; Duopoly model